2013
DOI: 10.1161/circimaging.112.000138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Therapeutic Benefit from Revascularization in Patients With Left Ventricular Systolic Dysfunction

Abstract: Background-Although the recent surgical treatment of ischemic heart failure substudy reported that revascularization of viable myocardium did not improve survival, these results were limited by the viability imaging technique used and the lack of inducible ischemia information. We examined the relative impact of stress-rest rubidium-82/F-18 fluorodeoxyglucose positron emission tomography identified ischemia, scar, and hibernating myocardium on the survival benefit associated with revascularization in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(109 citation statements)
references
References 31 publications
2
97
1
9
Order By: Relevance
“…Furthermore, the modalities used for imaging were dobutamine echocardiography and single photon emission computed tomography perfusion imaging which, although widely available, have lower sensitivity for hibernating myocardium than FDG PET, for which the extent of hibernating myocardium has also been shown to be a strong predictor of outcome benefit. [12][13][14][15]20,21 Finally, the patient population in the STICH trial differed from those in the PARR-2 study, in that the STICH population was younger, and had lower prevalence of prior CABG, renal dysfunction, and 3-vessel CAD (among those with angiography). 22 Therefore, the incremental value of the results of viability imaging was less because many of the patients in the STICH trial were already good candidates for CABG (having suitable anatomy was a requirement for inclusion).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the modalities used for imaging were dobutamine echocardiography and single photon emission computed tomography perfusion imaging which, although widely available, have lower sensitivity for hibernating myocardium than FDG PET, for which the extent of hibernating myocardium has also been shown to be a strong predictor of outcome benefit. [12][13][14][15]20,21 Finally, the patient population in the STICH trial differed from those in the PARR-2 study, in that the STICH population was younger, and had lower prevalence of prior CABG, renal dysfunction, and 3-vessel CAD (among those with angiography). 22 Therefore, the incremental value of the results of viability imaging was less because many of the patients in the STICH trial were already good candidates for CABG (having suitable anatomy was a requirement for inclusion).…”
Section: Discussionmentioning
confidence: 98%
“…[25,26] A 2013 study from the Cleveland Clinic reported outcomes for 648 consecutive ischaemic cardiomyopathy patients who underwent perfusion and metabolic imaging by PET. [26] Patients had a mean ejection fraction of 31%, and early revascularisation (within 92 days) was performed in 199 patients (33%). Patients were followed up for an average of 2.8 years for a primary endpoint of all-cause mortality.…”
Section: Viability Testing In Clinical Practice: Observational Seriesmentioning
confidence: 99%
“…[27] PARR-2 enrolled patients with severe left ventricular dysfunction and suspected coronary artery disease being considered for revascularisation or transplantation, and randomised them to FDG-PET imaging (n = 218) or stan- [26] dard of care (n = 212). The primary endpoint was a composite of cardiac death, MI or recurrent hospital stay.…”
Section: Parr-2 Trialmentioning
confidence: 99%
“…33 (patients undergoing early revascularization within 92 days of PET were excluded from analysis to avoid ''waiting-time'' bias).…”
Section: Pet: Hibernating (Viable) Myocardium Vs Inducible Ischemia Amentioning
confidence: 99%